Situating the “human” in forest landscape restoration - Mansourian, Stephanie; Djenontin, Ida N. S.; Elias, Marlène; Oldekop, Johan A.; Derkyi, Mercy Afua Adutwumwaa; Kull, Christian A.; Pacheco, Pablo (Frontiers in Environmental Science, 2025)
Globally, forest landscape restoration (FLR) is gaining ground, alongside other forms of restoration under the UN Decade on Ecosystem Restoration. In most cases, projects and initiatives fail to consider human dimensions that influence the processes and outcomes of the restoration effort. These dimensions refer to how and why humans value natural resources; how humans want resources to be managed; and how humans affect or are affected by natural resource management decisions. Using the model of the forest transition curve that shows the trajectory from loss of forests to restored forests, we discuss how FLR intersects in different ways with this transition curve. We conclude that: 1) definitions and their implications are a fundamental challenge for FLR; 2) there is an intrinsic interdependence between people and forests that varies across spatial and temporal scales and that is mediated by institutions; 3) power differentials among stakeholders create imbalances in restoration; 4) conflicts around restoration result from differing interests, power and values. Equitable and durable restoration requires a much greater inclusion of human dimensions along all steps of the process.